Bringing Pesantren into Diplomacy to Achieve the World Trust - Achmad Sururi (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Conflict conditions in the Middle East would affect the many eyes of the world. All the world's eyes will turn to the areas that are relatively more stable for security affairs. Souteast Asia is relatively calmer than the Middle East today. ASEAN condition that is peaceful enough turns the world's attention onto it. Indonesia in ASEAN is the ultimate driving machine. One common enemy in the international community today is terrorism. Terrorists who brought the doctrine of radicalism admittedly still exist in Indonesia. Discussing radicalism today can be done by anyone of any circles. However, what makes it uncomfortable is when associating radicalism with Islamic boarding school/ Pesantren. Radicalism in the name of religion, in some cases, is done by some